The concept of values and its importance in the educational process and its behavioral applications from the Islamic perspective” - Al Selimi, Ahlam Atik Magly (Journal of Educational and Psychological Sciences, 2019)
The study aimed at building a cognitive perception for the values and their characteristics. The study also mentioned some behavioral applications of the value system with the citation of the Quranic verses and the honest Hadiths. The researcher used the descriptive and deductive approaches. The study manipulates the concept of values ​​and its importance in the educational process and its behavioral applications from the Islamic perspective. The study is prepared through three aspects: The first aspect is showing the meaning of values ​​from the Islamic perspective and its trends. The second aspect includes a brief summary about the value system in Islam showing its traits, characteristics and importance The researcher presents in the third aspect some behavioral applications for the value system in Islam with its Islamic rooting, then the conclusion and results The study deduced some findings as: the fact that values play a key role in building human behavior. Moreover, values are important in building society. In addtion there are several trends for values . There are some who believe that values are standards that control behavior, and some others who believe that values are preferences for the individual which he can choose by himself, but the third trend sees values as the needs and the individual motives.